Mucoactive agents for chronic, non‐cystic fibrosis lung disease: A systematic review and meta‐analysis. Issue 6 (11th April 2017) - Tarrant, Benjamin J.; Le Maitre, Caitlin; Romero, Lorena; Steward, Ranjana; Button, Brenda M.; Thompson, Bruce R.; Holland, Anne E.
ABSTRACT: Inhaled mucoactive agents are used in respiratory disease to improve mucus properties and enhance secretion clearance. The effect of mannitol, recombinant human deoxyribonuclease/dornase alfa (rhDNase) and hypertonic saline (HS) or normal saline (NS) are not well described in chronic lung conditions other than cystic fibrosis (CF). The aim of this review was to determine the benefit and safety of inhaled mucoactive agents outside of CF. We searched Medline, Embase, CINAHL and CENTRAL for randomized controlled trials investigating the effects of mucoactive agents on lung function, adverse events (AEs), health‐related quality of life (HRQOL), hospitalization, length of stay, exacerbations, sputum clearance and inflammation. There were detrimental effects of rhDNase in bronchiectasis, with average declines of 1.9–4.3% in forced expiratory volume in 1 s (FEV1 ) and 3.7–5.4% in forced vital capacity (FVC) ( n  = 410, two studies), and increased exacerbation risk (relative risk = 1.35, 95% CI = 1.01–1.79 n  = 349, one study). Some participants exhibited a reduction in FEV1 (≥10–15%) with mucoactive agents on screening (mannitol = 158 of 1051 participants, rhDNase = 2 of 30, HS = 3 of 80). Most AEs were mild and transient, including bronchospasm, cough and breathlessness. NS eased symptomatic burden in COPD, while NS and HS improved spirometry, HRQOL and sputum burden in non‐CF bronchiectasis. Mannitol improved mucociliary clearance in asthma and bronchiectasis, while the effects of N‐acetylcysteine were unclear. In chronic lung diseases outside CF, there are small benefits of mannitol, NS and HS. Adverse effects of rhDNase suggest this should not be administered in non‐CF bronchiectasis.